2022
DOI: 10.1111/hex.13610
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the environment for engagement in health services: The Audit for Consumer Engagement (ACE) tool

Abstract: Introduction Although it is widely accepted that the physical environment can impact health quality and care outcomes, its impact on consumer engagement with health services has not been examined. Currently, no tools exist that assess the opportunities for consumer engagement offered within the physical environment. We aimed to develop and validate an environmental audit tool to assist health services and researchers to assess the extent to which the physical environment in health services creates and supports… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
2
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 51 publications
(122 reference statements)
0
2
2
Order By: Relevance
“…There is still a long way to go for consumers to gain strong engagement generally, but for CALD communities this challenge is pronounced. The analysis did not clearly identify physical environment as a factor for consumer engagement despite past earlier research suggesting otherwise (37).…”
Section: Discussioncontrasting
confidence: 64%
“…There is still a long way to go for consumers to gain strong engagement generally, but for CALD communities this challenge is pronounced. The analysis did not clearly identify physical environment as a factor for consumer engagement despite past earlier research suggesting otherwise (37).…”
Section: Discussioncontrasting
confidence: 64%
“…There is still a long way to go for consumers to gain strong engagement generally, but for CALD communities this challenge is pronounced. The analysis did not clearly identify the physical environment as a factor for consumer engagement despite past earlier research suggesting otherwise 40 …”
Section: Discussioncontrasting
confidence: 57%
“…The analysis did not clearly identify the physical environment as a factor for consumer engagement despite past earlier research suggesting otherwise. 40 For consumers from ethnic minority backgrounds, the availability of language support (in the form of interpreters) is imperative for effective consumer-provider communication. 41,42 This study identified that often nursing and allied health staff reported communicating with consumers from ethnic minority backgrounds during everyday care interactions (chemotherapy and radiotherapy treatment sessions, ad-hoc appointments and inpatient cancer care-related tasks)…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation